2018
DOI: 10.1111/fwb.13184
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter? Particle size vs. quality in bivalve suspension feeding

Abstract: Increases in total suspended solids (TSS) in rivers have likely contributed to the decline in unionid mussel population sizes as feeding and reproduction are reduced at high TSS concentrations. Surprisingly, however, unionids are often found in turbid rivers. We predicted that clay‐sized particles, which comprise > 80% of river seston (particles in suspension), were too small to affect unionid clearance rate (CR) and thus explain this conundrum. We examined this hypothesis in laboratory experiments involving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Lampsilis siliquoidea from the turbid river were less affected by increased TSS (i.e., smaller reduction in CR by increased TSS) compared to L. siliquoidea from the clear river at all water velocities. The results for the clear river mussels are consistent with similar reductions in CR that have been reported at these TSS concentrations for mussels from the Thames River (e.g., Tuttle‐Raycraft et al ; Tuttle‐Raycraft and Ackerman ). Furthermore, these results indicate that populations of mussels from turbid rivers have morphological/anatomical features that provide them the ability to live under high TSS concentration conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lampsilis siliquoidea from the turbid river were less affected by increased TSS (i.e., smaller reduction in CR by increased TSS) compared to L. siliquoidea from the clear river at all water velocities. The results for the clear river mussels are consistent with similar reductions in CR that have been reported at these TSS concentrations for mussels from the Thames River (e.g., Tuttle‐Raycraft et al ; Tuttle‐Raycraft and Ackerman ). Furthermore, these results indicate that populations of mussels from turbid rivers have morphological/anatomical features that provide them the ability to live under high TSS concentration conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Similar variation in gill anatomy has also been found among coexisting species of unionids in which denser cirral plates have been attributed to higher CR of smaller particles (Galbraith et al ). If this attribution is correct, then the denser cirral plates in our turbid river mussels would enable them to remove small‐sized particles that dominate the suspended load (i.e., clay and silt; Tuttle‐Raycraft and Ackerman ). Regardless, an increase in particle capture efficiency and/or particle sorting abilities of the turbid river mussels as a result of gill anatomy would facilitate their existence in turbid rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, data for volatile suspended solids were not available through the MNPCA website. Finally, Tuttle-Raycraft & Ackerman (2018) found that the size and quality of suspended solids may influence feeding rates in unionids. They found that clearance rates of mussels in a fine silt treatment were higher than for treatments of mixed sediment, clay or coarse silt.…”
Section: Attributed Highermentioning
confidence: 99%
“…In addition, other possible factors that could have caused or contributed to the reduction in concentration of F. columnare are, for example, competitive interactions between F. columnare and the microbiota present in and on the mussels (Rubiolo et al 2019) or antimicrobial properties in mussel mucus (Cilia & Fratini 2018). Filtration capacity in bivalves varies based on particle size and quality, among other things (Faust et al, 2009;Tuttle-Raycraft & Ackerman, 2018). Freshwater mussels can capture a wide range of particles sized 1-40 lm, including bacteria-at least large bacteria (Strayer, 2008).…”
Section: Discussionmentioning
confidence: 99%